Making art history : a changing discipline and its institutions - Mansfield, Elizabeth, 1965- (Routledge, 2007)
"Making Art History is a collection of essays by contemporary scholars on the practice and theory of art history as it responds to institutions as diverse as art galleries and museums, publishing houses and universities, school boards and professional organizations, political parties and multinational corporations. The text is split into four thematic sections, each of which begins with a short introduction from the editor, the sections include: Border Patrols, addresses the artistic canon and its relationship to the ongoing 'war on terror', globalization, and the rise of the Belgian nationalist party; The Subjects of Art History, questions whether 'art' and 'history' are really what the discipline seeks to understand; Instituting Art History, concerns art history and its relation to the university and raises questions about the mission, habits, ethics and limits of university today; and Old Master, New Institutions, shows how art history and the museum respond to nationalism, corporate management models and the 'culture wars'."--Publisher's description